Meniscal Repair Outcomes at Greater Than 5 Years: A Systematic Review and Meta-Analysis. (20th July 2022) - Nepple, Jeffrey J.; Block, Andrew M.; Eisenberg, Matthew T.; Palumbo, Noel E.; Wright, Rick W.
Abstract : Background: The utilization of meniscal repair techniques continues to evolve in an effort to maximize the rate of healing. Meniscal repair outcomes at a minimum of 5 years postoperatively appear to better represent the true failure rates. Thus, a systematic review and meta-analysis of the current literature was conducted to assess the rate of failure at a minimum of 5 years after meniscal repair. Methods: We performed a systematic review of studies reporting the outcomes of meniscal repair at a minimum of 5 years postoperatively. A standardized search and review strategy was utilized. Failure was defined as recurrent clinical symptoms or a meniscal reintervention to repair or resect the meniscus in any capacity, as defined by the study. When reported, outcomes were assessed relative to anterior cruciate ligament (ACL) status, sex, age, and postoperative rehabilitation protocol. Meta-analyses were performed with a random-effects model. Results: A total of 27 studies of 1, 612 patients and 1, 630 meniscal repairs were included in this review and meta-analysis. The pooled overall failure rate was 22.6%, while the failure rate of modern repairs (excluding early-generation all-inside devices) was 19.5%. Medial repairs were significantly more likely to fail compared with lateral repairs (23.9% versus 12.6%, p = 0.04). Failure rates were similar for inside-out (14.2%) and modern all-inside repairs (15.8%). Early-generation all-inside devices had a significantly higher failure rate (30.2%) compared with modern all-inside devices (15.8%, p = 0.01). There was no significant difference in meniscal failure rate between repairs with concomitant ACL reconstruction (21.2%) and repairs in ACL-intact knees (23.3%, p = 0.54). Conclusions: Modern meniscal repair had an overall failure rate of 19.5% at a minimum of 5 years postoperatively. Modern all-inside techniques appear to have improved the success rate of meniscal repair compared with use of early-generation all-inside devices. Lateral repairs were significantly more likely to be successful compared with medial repairs, while no difference was seen between patients undergoing meniscal repair with and without concomitant ACL reconstruction. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.